Transcriptional Control of Th9 Cells: Role of Foxo1 in Interleukin-9 Induction - Malik, Sakshi; Awasthi, Amit (Frontiers in Immunology, 2018)
Interleukin (IL) 9-producinghelper T (Th) 9 cells play a major role in contributing immunity against extracellular pathogens. In addition, role of Th9 cells was demonstrated in the pathogenesis of allergic, skin and intestinal inflammation. The functions of Th9 cells is further extended in anti-tumour immune response, as Th9 cells are suggested to be potent anti-tumour Th cells. Given pleotropic functions of IL-9 cells in various pathophysiological conditions, it is suggested to understand the differentiation and stability of Th9 cells and other IL-9-producing T cells. In addition to Th9 cells, Th2, Th17 and iTregs cells produce IL-9, but how IL-9 production is regulated in all these cell types is not clearly defined. Although Th2, Th9, Th17 and iTregs cells develop in the presence of distinct differentiating factors yet they all express IL-9 together with their own lineage specific cytokines. We summarize the current understanding of signalling pathways that lead to the promotion of differentiation of Th9 cells and IL-9 induction in Th2, Th17 and iTregs. Here in this review we discuss the role of transcriptional regulation of Th9 cells in context of our recent findings of Foxo1 as a new transcription factor required for the development and functions of Th9 and IL-9-producing T cells.